Mithraic centers on the road comunications in Croatia (parts of Roman Dalmatia, Pannonia Inferior, Pannonia Superior and Histria) : the example of Mursa - Lipovac-Vrkljan, Goranka (Ptuj : Pokrajinski muzej : Zgodovinsko društvo, 2001)
Zusammenfassung
Povzetek
P. o.: Archaeologia Poetovionensis ; 2, 2001
Bibliografija: str. 243-245 i uz tekst
Keywords: kult Mitre; Mitra; mitraizam; mitrijski reljefi; rimske ceste